2011
DOI: 10.1055/s-0031-1295648
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Poractant Alfa versus Beractant in the Treatment of Preterm Infants with Respiratory Distress Syndrome

Abstract: We prospectively evaluated the differences in clinical responses and short-term outcomes in preterm infants with respiratory distress syndrome (RDS) treated with poractant alfa or beractant. Premature infants with RDS were randomized to poractant alfa or beractant treatment between July 2008 and June 2009. Patients were followed until 40 weeks of corrected gestational age or death. The fraction of inspired oxygen (Fio(2)) after surfactant treatment, need for repeat doses, and duration of respiratory support an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 18 publications
5
53
1
3
Order By: Relevance
“…Different surfactants might vary in their suitability for nebulization, which is reflected by the great quantity of different preparations of surfactant that have been tested in both animal and clinical studies (12). In our study, we used Poractant alfa, an animal-derived surfactant which proved to be advantageous compared to different surfactant preparations regarding rapid onset of action, less need for redosing, and higher survival free of BPD in preterm infants (28), and regarding mortality (29) after bolus administration. Recently, an artificial surfactant aerosolized in a piglet model of acute lung injury resulted in improved gas exchange (30).…”
Section: Surfactant Distribution Relative To Wholementioning
confidence: 99%
“…Different surfactants might vary in their suitability for nebulization, which is reflected by the great quantity of different preparations of surfactant that have been tested in both animal and clinical studies (12). In our study, we used Poractant alfa, an animal-derived surfactant which proved to be advantageous compared to different surfactant preparations regarding rapid onset of action, less need for redosing, and higher survival free of BPD in preterm infants (28), and regarding mortality (29) after bolus administration. Recently, an artificial surfactant aerosolized in a piglet model of acute lung injury resulted in improved gas exchange (30).…”
Section: Surfactant Distribution Relative To Wholementioning
confidence: 99%
“…2,4 Given that mobile phones are now an integral part of most hospitals, guidelines for decontamination of mobile phones should be developed.…”
Section: Referencesmentioning
confidence: 99%
“…1 As with other environmental surfaces, prior studies have suggested that mobile phones may serve as a reservoir for pathogenic bacteria. 2 Given the difference in bacterial epidemiology, it is of interest to evaluate the type of bacteria found on the mobile phones of healthcare workers in a paediatric ward.…”
Section: Dear Editor Mobile Phones As a Potential Vector Of Infectiomentioning
confidence: 99%
See 2 more Smart Citations